2015
DOI: 10.1021/la504599b
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Nanosilica Dispersants for Carbon Nanotube

Abstract: Nanosilicas can disperse single-wall carbon nanotube (SWCNT) in aqueous solution efficiently; SWCNTs are stably dispersed in aqueous media for more than 6 months. The SWCNT dispersing solution with nanosilica can produce highly conductive transparent films which satisfy the requirements for application to touch panels. Even multiwall carbon nanotube can be dispersed easily in aqueous solution. The highly stable dispersion of SWCNTs in the presence of nanosilica is associated with charge transfer interaction wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 49 publications
0
26
0
Order By: Relevance
“…Recent supermolecular chemistry approaches have offered a powerful route for the reversible and controllable dispersion of SWCNT [15,16]. However, there has been little research on inorganic dispersants for SWCNT; our preceding study showed that nanosilica can disperse SWCNT, but loses its 3 dispersibility over time [17]. Thus, the inorganic SWCNT dispersant of sufficient stability should offer a new application field of SWCNT.…”
Section: Introductionmentioning
confidence: 96%
“…Recent supermolecular chemistry approaches have offered a powerful route for the reversible and controllable dispersion of SWCNT [15,16]. However, there has been little research on inorganic dispersants for SWCNT; our preceding study showed that nanosilica can disperse SWCNT, but loses its 3 dispersibility over time [17]. Thus, the inorganic SWCNT dispersant of sufficient stability should offer a new application field of SWCNT.…”
Section: Introductionmentioning
confidence: 96%
“…We have found that nanosilica can be used as an efficient dispersant for carbon nanotubes. 27 However, its dispersibility changes with aging time, which is not desirable for the TCF fabrication. Then, we developed a quite stable Zn/Al complex dispersant for the fabrication of SWCNT based film.…”
Section: Introductionmentioning
confidence: 99%
“…19 The hydrophilic nature of charged sulfonate groups being accessible by bulk water helps the exfoliation and the stabilization of individual SWCNTs come through their electrostatic repulsion. 9 TEM and AFM were utilized to characterize the length and diameter of the SWCNTs dispersion. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For past few decades, carbon nanotubes (CNTs) are considered as a promising material in various elds including energy, environment, medicine, and textiles because of their unique and outstanding properties such as good electrical properties, high mechanical and thermal stability. [1][2][3][4][5][6][7][8][9][10][11] In particular, singlewalled carbon nanotubes (SWCNTs), which have remarkable electrical mobility, conductivity 6,12 and work functions, 13 are deliberated favorable in electrical applications such as transistors, 6,14,15 sensors, 16,17 memory devices 18 and conducting lms. [4][5][6][7][19][20][21] Thus, SWCNTs are expected as the best candidate material to replace current ITO due to outstanding exibility, good stability, high conductivity and good optical transparency, ability of low-temperature printing and coating process; and thanks to its abundant availability which has great potential for the cost reduction.…”
Section: Introductionmentioning
confidence: 99%